Chemical Composition of Guava Leaf Extract and Lipid Oxidation Inhibition in Chinese Sausage During Storage - Jumnaksan, Siriwan (Journal of Food Technology, Siam University, 2019)
This research aims to study the chemical composition, antioxidative properties of the guava leaf extract powder and its antioxidant activities in Chinese sausage during storage at room temperature (30±3°C) for 28 days varying the guava leaf extract powder at 5 levels (0.05, 0.10, 0.15, 0.20 and 0.25 percent by pork meat weight) comparing with 0.01 percent synthetic antioxidants (BHT). The results showed that the value of lightness (L*), redness (a*) and yellowness (a*) of the extract of guava leaf powder with moisture content of 9.94 percent by wet basis were 46.64, 2.10 and 17.24 respectively. The amount of protein, fat, ash, fiber and carbohydrate were 6.89, 0.57, 11.16, 0.02 and 71.41 percent (dry basis), respectively. Total phenolic compounds were 273.98 mg Gallic Acid Equivalent /g extract. The radical scavenging activity by DPPH assay was 0.08 g DPPH/mg of sample which was statistically not significant difference (p>0.05) comparing with the radical scavenging activity of BHT (0.09 g DPPH/mg). When tracking the change of PV, TBA value and sensory evaluation of Chinese sausage, the results showed that Chinese sausage with 0.05 to 0.25 percent guava leaf extract powder had antioxidative properties comparing with control. However, it was lower than Chinese sausage with 0.01 percent BHT. In addition, Chinese sausage with 0.25 percent guava leaf extract and storage at 21 day was unacceptable from the consumers because of the reduction of sensory quality in the color attribute.